2019
DOI: 10.3892/etm.2019.7792
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Urtica�macrorrhiza Hand.‑Mazz. polysaccharides to protect against cyclophosphamide‑induced intestinal immunosuppression

Abstract: As a strategy to prevent the well-known immunosuppressant effects of cyclophosphamide (CY), the immunomodulatory activity of the polysaccharide isolated from Urtica macrorrhiza Hand.-Mazz. (UMHMPS) was investigated in the present study. The chemical properties of UMHMPS, including total carbohydrates, uronic acid, protein contents, monosaccharide compositions, molecular weight and structural confirmation, were investigated. The immunomodulatory activity of UMHMPS was evaluated using a CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Studies have demonstrated that CY destroys intestinal mucosal system by reducing barrier function, injuring intestinal villi and crypts, inhibiting secretion of sIgA and damaging Peyer’s patch ( Miao et al, 2015 ; Zhao et al, 2016 ; Wang Z et al, 2019 ). In gastrointestinal mucosal barrier, goblet cells continually produce mucins to replenish and maintain the mucus barrier, where some chemical composition like sIgA is higher concentrated ( Ouwerkerk et al, 2013 ; Cornick et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that CY destroys intestinal mucosal system by reducing barrier function, injuring intestinal villi and crypts, inhibiting secretion of sIgA and damaging Peyer’s patch ( Miao et al, 2015 ; Zhao et al, 2016 ; Wang Z et al, 2019 ). In gastrointestinal mucosal barrier, goblet cells continually produce mucins to replenish and maintain the mucus barrier, where some chemical composition like sIgA is higher concentrated ( Ouwerkerk et al, 2013 ; Cornick et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although CY is an alkylating drug used on cancer and autoimmune disease, it has been used as an immunosuppression-inducing agent due to its major side effect ( Wang Z et al, 2019 ). In this study, a stable and classical CY-induced immunosuppression model was used to evaluate the recovery effect of CPPF on both intestinal immunity and microbiota modulation, according to several previous studies ( Tang et al, 2018 ; Zhu et al, 2018 ; Wang Z et al, 2019 ). The mice were divided into five groups, 12 mice each.…”
Section: Methodsmentioning
confidence: 99%